2016
DOI: 10.4028/www.scientific.net/msf.858.105
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron X-Ray Topography Analysis of Double Shockley Stacking Faults in 4H-SiC Wafers

Abstract: Synchrotron white beam X-ray topography studies carried out on 4H-SiC wafers characterized by locally varying doping concentrations reveals the presence of overlapping Shockley stacking faults generated from residual surface scratches in regions of higher doping concentrations after the wafers have been subjected to heat treatment. The fault generation process is driven by the fact that in regions of higher doping concentrations, a faulted crystal containing double Shockley faults is more stable than perfect 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…BPSB Observation with BSF-like Geometry. Prior studies have demonstrated that BSFs are formed by terrace nucleation as another polytype or by deflection of threading dislocations [4]. In contrast, BPSBs are formed by thermal stress and Frank-Read sources in the basal plane [6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BPSB Observation with BSF-like Geometry. Prior studies have demonstrated that BSFs are formed by terrace nucleation as another polytype or by deflection of threading dislocations [4]. In contrast, BPSBs are formed by thermal stress and Frank-Read sources in the basal plane [6].…”
Section: Resultsmentioning
confidence: 99%
“…Among several applications, 4H SiC has attracted particular interest for power electronics because of intrinsic advantages such as higher temperature operation and reduced switching losses compared to conventional silicon-based devices [1]. On the other hand, limited process control over the densities of various crystalline defects in SiC, including basal plane dislocations (BPDs) [2,3] and bar stacking faults (BSFs) [4], can significantly impact device yields. Synchrotron X-ray topography (XRT) has been applied for highly sensitive characterization of crystalline defects in PVT-grown SiC [5].…”
Section: Introductionmentioning
confidence: 99%
“…The topography rules are that the pairs of Si-core PDs appear as bright contrast and the pairs of C-core PDs appear as dark contrast under the diffraction of = g 1128. [11][12][13] It has been suggested that the DSF formation is triggered by the mechanical damage on the crystal surface. 8,14,15) The first suggestive result for the relation between the damage and DSF nucleation was reported by Irmscher et al 13) After they annealed a heavily doped SiC crystal with local scratching on the surface, DSFs were found to have formed only in the damaged regions.…”
Section: Introductionmentioning
confidence: 99%
“…15,16) In addition, it is known that the DSFs expand mainly though gliding of the Si-core PD pairs. [11][12][13]17) Although shear stress is often responsible for the dislocation glide on the slip plane, [18][19][20] the driving force relating to the localized electronic states around the faulted planes has been proposed for the DSF expansion.…”
Section: Introductionmentioning
confidence: 99%